1996
DOI: 10.1002/(sici)1099-1581(199602)7:2<108::aid-pat453>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Properties of Polyacrylic Acid Derivative - Eu3+ Ion - Low Molecular Ligand Complexes

Abstract: The polyacrylic acid derivative, the copolymer (PABAM) of acrylic acid (AA) and p‐benzoic acid acrylamide (BAM) were prepared by polymeric reaction. The coordinate structure of the polymer–Eu3+ complexes was characterized by X‐ray photoelectron spectroscopy. The fluorescence intensity of the PABAM–Eu3+ complex was enhanced because of introduction of a BAM unit in the polyacrylic acid and reached a maximum when the mole ratio of AA to BAM was about 1 : 1. The ternary complexes of Eu3+–polymer–1,10‐phenanthrolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the case of the polymer/metal composites, they showed a broadband ranging absorption only, and the excitation wavelength was about 389 nm. The reason for this is that the details of the rare earth metal excitation and emission spectra are particularly sensitive to structural details of the coordination environment [53][54][55][56][57][58]. These results also indicated that the structures of the Eu and Sm complexes were changed and that they bonded with dithiocarbamate units.…”
Section: Synthesis Of Fluorescent Polymer/metal Composites By Selfassmentioning
confidence: 99%
“…In the case of the polymer/metal composites, they showed a broadband ranging absorption only, and the excitation wavelength was about 389 nm. The reason for this is that the details of the rare earth metal excitation and emission spectra are particularly sensitive to structural details of the coordination environment [53][54][55][56][57][58]. These results also indicated that the structures of the Eu and Sm complexes were changed and that they bonded with dithiocarbamate units.…”
Section: Synthesis Of Fluorescent Polymer/metal Composites By Selfassmentioning
confidence: 99%
“…Although considerable efforts have been expended on diverse studies of Eu 3+ –polyelectrolyte composites because of their promising application for plastic fluorescence materials,1–3 the corresponding ternary composite containing a second ligand besides polyanions has not yet been fully investigated and had been mainly observed in cases where the second ligand was dispersed in the polymer matrix. In those attempts—(1) research on the effect of low molecular weight ligands on the fluorescence properties of Eu 3+ –polyelectrolytes4, 5 and 2 study of Eu 3+ ‐linear and ‐branched polymers containing β ‐diketone moieties in the chain6— the weak fluorescence was attributed to a structural factor. It is hoped that the introduction of the second ligand into the coordination sphere of Eu 3+ by releasing precoordinated water molecules may be an efficient way to enhance fluorescence.…”
Section: Introductionmentioning
confidence: 99%